Positioning “the people” and Its Enemies: Populism and Nationalism in AfD and UKIP - Breeze, Ruth (Javnost-The Public, 2019)
Much previous research on right-wing populist parties in Europe has concentrated on what they share, and has failed to problematise the term “populist.” This article sets out from one proposed distinction between populism and nationalism, comparing the discourses of two relatively under-researched parties: Alternative für Deutschland (AfD) and the United Kingdom Independence Party (UKIP). Analysis of the way these two parties operationalise both a vertical (populist) and horizontal (nationalist) axis brings out some differences, as well as major areas of overlap. The conclusions suggest that such parties activate hostility to elites (populism) in order to destabilise the political landscape, while boosting support for anti-migrant and anti-EU stances (nationalism). The vertical axis is particularly powerful because it exploits pre-existing sources of resentment or suspicion and enables the people to be positioned as “victims,” thereby legitimating their attacks on “others” who threaten the people's space.